2019
DOI: 10.1002/adsc.201801586
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed C(sp2)−C(sp3) Kumada Cross‐Coupling of Aryl Tosylates with Alkyl Grignard Reagents

Abstract: Aryl tosylates are an attractive class of electrophiles for cross-coupling reactions due to ease of synthesis, low price, and the employment of CÀ O electrophiles, however, the reactivity of aryl tosylates is low. Herein, we report the Ni-catalyzed C(sp 2 )À C(sp 3 ) Kumada cross-coupling of aryl tosylates with primary and secondary alkyl Grignard reagents. The method delivers valuable alkyl arenes by cross-coupling with challenging alkyl organometallics possessing β-hydrogens that are prone to β-hydride elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…Kambe's 2003 report suggested that nickel is less selective than Pd in Kumada couplings of chloroalkyl (or bromoalkyl) tosylates [52] . This observation was corroborated by a separate study by Szostak in 2019 [56] . In the presence of a Ni/dppe catalyst, 1‐chloronaphthalene and 1‐naphthyl tosylate react with an alkyl Grignard reagent at essentially identical rates, resulting in about 50 % recovery of each starting material (Scheme 20).…”
Section: Divergent Selectivity Between a Halide And A Pseudohalidementioning
confidence: 53%
See 2 more Smart Citations
“…Kambe's 2003 report suggested that nickel is less selective than Pd in Kumada couplings of chloroalkyl (or bromoalkyl) tosylates [52] . This observation was corroborated by a separate study by Szostak in 2019 [56] . In the presence of a Ni/dppe catalyst, 1‐chloronaphthalene and 1‐naphthyl tosylate react with an alkyl Grignard reagent at essentially identical rates, resulting in about 50 % recovery of each starting material (Scheme 20).…”
Section: Divergent Selectivity Between a Halide And A Pseudohalidementioning
confidence: 53%
“… A nickel/dppe‐catalyst does not discriminate between an aryl tosylate and chloride during a Kumada coupling [56] …”
Section: Divergent Selectivity Between a Halide And A Pseudohalidementioning
confidence: 99%
See 1 more Smart Citation
“…Szostak and co-workers reported the Kumada-Tamao-Corriu cross-coupling of aryl tosylates 32 with alkyl Grignard reagents 14Cl in the presence of the stable NiCl 2 (dppe) precatalyst (Scheme 15). 43 Li and coworkers, however, achieved the Ni(acac) 2 -catalyzed crosscoupling of aryl tosylates 32 with aryl Grignard reagents 14Cl promoted by LiCl. 44 They demonstrated that LiCl accelerated the reduction of Ni(II) to Ni(0).…”
Section: Scheme 14 Ni-catalyzed Ligand-free Reaction Of Aryl Bromidesmentioning
confidence: 99%
“…Furthermore, aryl sulfonate esters play an important role in organic chemistry as synthetic intermediates, which is related to their versatile application as protecting groups and C–O electrophiles in organic reactions. The resistance of the sulfonate groups to various reaction conditions makes them handy protecting groups for phenols [ 30 , 31 ], while the possibility to activate the C–O bond using transition metal catalysis makes them a valuable alternative to aryl halides in cross-coupling reactions [ 32 , 33 , 34 , 35 , 36 ]. It is worth noting that in both variants, the resulting target products do not contain a sulfonate ester moiety, which is deconstructed under basic or transition-metal-catalyzed conditions.…”
Section: Introductionmentioning
confidence: 99%